Starbucks Coffee Company: coffee cafe company / Muhammad Aliff Aminuddin ... [et al.] - Aminuddin, Muhammad Aliff; Abdullah, Nor Faidah; Mazlan, Nurul Aqilah; Mohd Idris, Aleesya Aina; Mustafa, Ahmad Naqiuddin (2021)
For our case study, we would like to summarize Starbucks Coffee Company which is a coffee cafe company. This cafe company is very familiar especially for the university student, businessman or businesswoman to be a place for discussion. The location of the company is very strategic in the big town and at the place where there is high demand from people around. Starbuck easy to find at the big malls such as AEON mall, Setia City Mall, One Utama, etc. Starbucks coffee provides high quality coffee, performance enhanced, with the affordable price. They have the highest quality coffee in the world, and the way we engage with our customers and communities to do business responsibly and make sure everything we do honors that connection. In 1971, their story has begun. With a single location in Seattle's Pike Place Market, they were a roaster and retailer of whole bean and ground coffee, tea, and spices back then. Every day, they have the privilege of connecting with millions of clients. Starting with its employees, Starbucks Coffee "inspires and nurtures the human spirit." To fulfil this part of its goal statement, the company maintains a small-company culture that emphasizes rapport and warmth. Starbucks Coffee's corporate culture is thus directly influenced by its corporate objectives in 76 markets. In addition, the company's mission statement includes a section on customer experience. Customers benefit from the company's pleasant, small-business atmosphere. At Starbucks cafés, for example, personnel and customers are addressed by their first names. In addition, the design of these coffeehouses aspires for comfort and warmth. These methods encourage employees and customers to form meaningful and friendly relationships. Another aspect of Starbucks Coffee's business mission statement to consider is that it suggests a personalized and gradual approach. The “one person, one cup, and one neighborhood at a time” component demonstrates how the organization guarantees that each employee and customer has a significant impact. This component of the company vision also means that Starbucks Coffee intends to build the business slowly and steadily, one location or area at a time.